Immune Monitoring Using QuantiFERON®-CMV Assay in Congenital Cytomegalovirus Infection: Correlation With Clinical Presentation and CMV DNA Load. (5th June 2020) - Capretti, Maria Grazia; Marsico, Concetta; Chiereghin, Angela; Gabrielli, Liliana; Aceti, Arianna; Lazzarotto, Tiziana
Abstract: Background: Cytomegalovirus (CMV)-specific CD8 + T-cell responses can be detected early in fetal life, but their role in the manifestations of congenital CMV (cCMV) infection remains largely unknown. Methods: CMV-specific CD8 + T-cell responses were assessed in neonates with cCMV using QuantiFERON ® -CMV assay, within day 14 of life (T0 ) and during the second month of life (T1 ). Detection and quantification of CMV DNA in whole blood and urine samples were performed at both time points. QuantiFERON ® -CMV results were evaluated in relation to timing of maternal infection, clinical manifestations of cCMV and CMV DNA levels. Results: Thirty neonates were enrolled (10/30 [33%] symptomatic; 20/30 [67%] asymptomatic). At T0 16/30 (53%) subjects had a reactive QuantiFERON ® -CMV result and 16/16 (100%) were asymptomatic, whereas 14/30 (47%) had a nonreactive or indeterminate QuantiFERON ® -CMV result and 4/14 (29%) were asymptomatic. At T1, 17/29 (59%) subjects had a reactive QuantiFERON ® -CMV result, and 17/17 (100%) were asymptomatic, whereas 12/29 (41%) had a nonreactive or indeterminate result and 3/12 (25%) were asymptomatic. At both T0 and T1 reactive QuantiFERON ® -CMV results correlated with lack of symptoms ( P = .0001). At T1 median CMV DNAemia was lower in subjects with reactive QuantiFERON ® -CMV results as compared with subjects with nonreactive or indeterminate results (1.82 log IU/mL [1.82–2.89] vs 2.55 log IU/mL [1.82–4.42], P = .009). No correlation was found between QuantiFERON ® -CMV results and gestational age at maternal infection nor with urine CMV DNA levels. Conclusions: A detectable CMV-specific CD8 + T-cell response, evaluated using the QuantiFERON ® -CMV assay, correlates with the lack of CMV-related symptoms and the control of CMV DNAemia. Abstract : In congenital cytomegalovirus (CMV) infection a detectable cell-mediated immunity, as evaluated using the QuantiFERON ® -CMV assay, correlates with the lack of symptoms and with the control of CMV DNAemia.